Chromatically independent, two-color uncaging of glutamate and GABA with one- or two-photon excitation. - Passlick, Stefan (Methods Enzymol, 2019)
Caged compounds enable fast, light-induced, and spatially-defined application of bioactive molecules to cells. Covalent attachment of a caging chromophore to a crucial functionality of a biomolecule renders it inert, while short pulses of light release the caged molecule in its active form. Caged neurotransmitters have been widely used to study diverse neurobiological processes such as receptor distribution, synaptogenesis, transport, and long-term potentiation. Since the neurotransmitters glutamate and gamma-aminobutyric acid (GABA) are the most important, they have been studied extensively using uncaging. However, to be able to probe their interactions on a physiologically relevant timescale, fast and independent application of both neurotransmitters in an arbitrary order is desired. This can be achieved by combining two caging chromophores absorbing non-overlapping and thus orthogonal wavelengths of light, which enables the precise application of two caged molecules to the same preparation in any order, a technique called two-color uncaging. In this chapter, we describe the principles of orthogonal two-color uncaging with one- and two-photon excitation with an emphasis on caged glutamate and GABA. We then give a guide to its practical application and highlight some key studies utilizing this technique.